The Role of Judicial Accounting Techniques in Developing Accounting Work Mechanisms to Detect Material Misstatements in the Financial Statements: A Field Study - Abd-Elghaffar, Nourhan EL-Sayed Mohammed (The Arab Journal of Administration, 2025)
The main objective of this research is to provide a future vision on the impact of the integration between the use of open book accounting (OBA) and the value stream costing (VSC) system in supporting the approach of cost management across organizational boundaries and improving strategic cost planning mechanisms through a field study on Egyptian businesses. The research seeks to identify the extent to which enterprises are aware of the concept of the open book accounting, and the value stream costing system, and its role in reducing cost and supporting the cost management approach across organizational boundaries to improve strategic cost planning mechanisms. The study found that the open book accounting method plays an important role in supporting and activating the value stream cost system. This is done by eliminating factors that affect the efficiency of product flow in the value stream in the supply chain in a lean production environment. The research recommends that Egyptian organizations adopt introductory and training programs and courses to prepare specialized cadres in the field of cost accounting and management accounting. In addition to develop their efficiency, raise their professional level, qualify them to deal with and apply the practices and work of the open accounting records method, and increase their awareness about the benefits that can be achieved from adopting these practices and businesses, and develop appropriate frameworks and controls to regulate these practices and businesses also, through holding conferences, seminars and workshops, beside, issuing awareness bulletins, and consolidating the concept of a culture of change and development and the importance of applying Modern methods of cost management in a lean production environment.